2010
DOI: 10.1530/eje-10-0043
|View full text |Cite
|
Sign up to set email alerts
|

FSHR gene polymorphisms influence bone mineral density and bone turnover in postmenopausal women

Abstract: Objective: FSH, via its receptor (FSHR), influences bone remodeling and osteoclast proliferation and activity. The aim of this study was to evaluate the influence of two single nucleotide polymorphisms (SNPs) of the FSHR gene on bone mineral density (BMD) and bone turnover markers (bone alkaline phosphatase and type I collagen C-telopeptides) in postmenopausal women. Methods: Two hundred and eighty-nine unrelated postmenopausal women were genotyped for the SNPs rs1394205 and rs6166. BMD was estimated using dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 39 publications
5
56
0
1
Order By: Relevance
“…Patients with functional hypothalamic amenorrhea, in whom both FSH and estrogen are low, show slight to moderate skeletal defects (20). In contrast, women harboring an activating FSHR polymorphism, rs6166, have lower bone mass and higher bone resorption rates (8). Consistent with these human studies, the injection of FSH into rats has been shown to augment ovariectomy-induced alveolar bone loss (21).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Patients with functional hypothalamic amenorrhea, in whom both FSH and estrogen are low, show slight to moderate skeletal defects (20). In contrast, women harboring an activating FSHR polymorphism, rs6166, have lower bone mass and higher bone resorption rates (8). Consistent with these human studies, the injection of FSH into rats has been shown to augment ovariectomy-induced alveolar bone loss (21).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, amenorrheic women with high FSH levels >35 IU/L display greater decrements in bone density than those with a mean FSH of ∼8 IU/L (7). Likewise, women having activating FSH receptor (FSHR) polymorphisms have a low bone mass and high bone turnover (8). Together, these findings suggest that a rising FSH level may, in part, contribute to the perimenopausal bone loss that has traditionally been attributed solely to reduced estrogen levels.…”
mentioning
confidence: 99%
“…Likewise, in a recent study, patients with functional hypothalamic amenorrhea, in whom both FSH and estrogen were low, showed slight to moderate skeletal defects [12]. Furthermore, women harboring an activating FSH receptor (FSHR) polymorphism, rs6166, have lower bone mass and higher resorption markers [13]; this attests to a role for FSHRs in human physiology, and perhaps, even human pathophysiology. Consistent with these human studies, exogenously administration of FSH to rats augmented ovariectomy-induced bone loss [14,15].…”
Section: Introductionmentioning
confidence: 93%
“…The results were impressive: the authors found that the single nucleotide polymorphism (SNP) rs6166 of the FSHR gene significantly influenced bone mass in postmenopausal women (29). Prior studies on AA rs6166 have associated this polymorphism with increased stimulation of the ovarian FSHR.…”
mentioning
confidence: 99%
“…Osteoporosis is a multifactorial disorder with genetic variation accounting for up to 80% variation in bone mineral density (28). Rendina et al sought to tie the role of FSH in causing osteoporosis to the genetic variability that exists among the human population (29). To do so, they examined 289 postmenopausal women for FSHR polymorphisms at two sites, rs1394205 and rs6166, and then analyzed the influence these polymorphisms had on bone mass and bone turnover (29).…”
mentioning
confidence: 99%